2023
DOI: 10.1111/poms.13702
|View full text |Cite
|
Sign up to set email alerts
|

Hospital admission, facility‐based isolation, and social distancing: An SEIR model with constrained medical resources

Abstract: COVID-19 is a highly contagious disease that has spread to most countries at unprecedented transmission speed. Medical resources and treatments provided by the healthcare system help reduce the mortality rate and spread of COVID-19 by isolating infectious individuals. We introduce a modified SEIR model that considers individuals access to limited medical resources to characterize the central role of medical resources during the pandemic. We discuss how the three hospital admission policies (hierarchy, mixed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Z. Chen and Kong (2023) and Gonçalves et al (2023) propose deterministic compartmental models, which include hospitalized and critically ill patients.…”
Section: Capacity Demand Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Z. Chen and Kong (2023) and Gonçalves et al (2023) propose deterministic compartmental models, which include hospitalized and critically ill patients.…”
Section: Capacity Demand Modelingmentioning
confidence: 99%
“…In the supply‐focused literature, demand is modeled with compartmental or queuing models. Z. Chen and Kong (2023) and Gonçalves et al. (2023) propose deterministic compartmental models, which include hospitalized and critically ill patients.…”
Section: Contribution To the Literaturementioning
confidence: 99%
“…Chen and Kong (2023) develop and test a model to study the impact of medical resources on reducing cumulative deaths and containing the virus while allowing for a capacity constraint on hospital beds. The model adds two state variables to the classic SEIR model to yield a SEIRHQD structure, Susceptible (S) Exposed (E), Infectious (I), Recovered (R), Hospitalized (H), Quarantined (Q), and Death (D).…”
Section: Hospital Operations/capacitymentioning
confidence: 99%
“…We accepted four papers that deal with hospital capacity and operations. These include: “Pausing transplants in the face of a global pandemic: Patient survival implications” (Zhang et al., 2023), “Hospital Admission, Facility‐based Isolation, and Social Distancing: An SEIR Model with Constrained Medical Resources” (Chen & Kong, 2023), “Managing Medical Equipment Capacity with Early Spread of Infection in a Region” (Jain & Rayal, 2023), and “Operations (Management) Warp Speed: Rapid Deployment of Hospital‐Focused Predictive/Prescriptive Analytics for the COVID‐19 Pandemic” (Shi et al., 2023).…”
Section: Hospital Operations/capacitymentioning
confidence: 99%
“…Chehrazi et al (2019) investigated an optimal control problem for a susceptible‐infected‐susceptible (SIS) model of an infectious disease with resistance and demonstrated that the optimal prescription policy is of the bang‐bang type with a single switching time. Chen and Kong (2022) studied the effects of different hospital admission policies on the spread of infectious diseases using a modified susceptible‐exposed‐infected‐recovered (SEIR) model under a static social distancing policy. Additionally, (El Housni et al, 2022a; El Housni et al, 2022b) developed new compartmentalized models to study the effects of testing capacity and social distancing measures on the pandemic in New York City and North Carolina.…”
Section: Literature Reviewmentioning
confidence: 99%